PEMIKIRAN ABDULLAH SAEED TENTANG RIBA DAN IMPLIKASINYA TERHADAP HUKUM BUNGA BANK - Niken Juliana; Y Sonafist; Nuzul Iskandar (Institut Agama Islam Negeri Batusangkar, 2021)
When the discussion about the prohibition of bank interest law was crowded, Abdullah Saeed came up with an alternative thought. For Saeed, bank interest does not fall into the category of riba as many voices say today. Therefore, this study aims to answer several questions: how is the concept of riba in Saeed's thinking; how is that thought correlated with the law of bank interest; and what is the legal methodology that Saeed used to produce his opinion. To answer this question, this study uses a literature source in the form of Abdullah Saeed's writings and is supported by other relevant sources. Analysis and presentation of data is a descriptive-analytic. This study finds that according to Saeed, the interest system applied by modern banking is completely different from the riba system at the time of the Prophet Muhammad that actually has its roots in pre-Islamic times. In expressing this opinion, Saeed uses a historical approach to the texts that talk about riba, then uses the theory of wisdom which in some respects is similar to the theory of qiyas in the terminology of conventional Islamic law.